Analisis Kemampuan Membaca Pemahaman Dengan Mengapresiasi Cerpen Pada Siswa Kelas V Sekolah Dasar - Nuraida, Indri Rahmawati; Nuriyanti, Risma; Widyaningsih, Yennie Indriati; Adiredja, Rajji K.; Wasilah, Ulni (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Reading comprehension is a  fundamental skill essential for student success in various subjects. However, many students still experience difficulty understanding the content of reading material. This study aims to analyze fifth-grade elementary  school students’ reading comprehension skills through short story  appreciation. This study employed  a quqlitative method with a case study design. The subjects were 15  fifth-grade students. Data collection used a descriptive test that  measured four indicators:  the ability to answer questions about the short story’s  content, identify  difficult words and there meanings, identify  the meaning idea/main idea of each paragraph, and retell the shorts story in their own words.  Data analiysis  was conducted using the triangulation technique according to Miles and Huberman,  encompassing data reduction, data  presentation, and conclusions drawing. The overall analysis showed an average score was 65,6 for students,   concluding that students’ reading comprehension skills  through short story appreciation are in the sufficient category.Membaca pemahaman merupakan keterampilan dasar yang penting untuk menunjang keberhasilan belajar siswa di berbagai mata pelajaran. Namun demikian, masih banyak siswa yang mengalami kesulitan dalam memahami isi bacaan. Penelitian ini bertujuan untuk menganalisis kemampuan membaca pemahaman siswa dengan mengapresiasi cerpen pada siswa kelas V sekolah dasar. Penelitian ini menggunakan metode kualitatif dengan desain studi kasus. Subjek penelitian ini adalah siswa kelas V yang berjumlah 15 orang. Teknik pengumpulan data menggunakan tes uraian yang merujuk pada empat indikator, yaitu kemampuan menjawab pertanyaan isi cerpen, menemukan kata sulit dan artinya, menemukan ide pokok/gagasan pokok setiap paragraf, dan menceritakan kembali isi cerpen menggunakan bahasa sendiri. Analisis data dilakukan menggunakan teknik triangulasi menurut Miles and Huberman, meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil analisis secara keseluruhan rata-rata siswa memperoleh skor 65,6, sehingga dapat disimpulkan bahwa kemampuan membaca pemahaman siswa dengan mengapresiasi cerpen berada pada kategori cukup.